Approaches to therapy and prevention of frailty in the light of contemporary medicine - Bujnowska-Fedak, Maria Magdalena; Waligóra, Joanna; D’Avanzo, Barbara; Holland, Carol; Kurpas, Donata (Family Medicine & Primary Care Review, 2017)
Over the last several decades, the growing number of patients with geriatric problems has become a serious challenge for primary care physicians. Frailty is an often encountered condition in older age. This is a state of increased vulnerability and loss of total physiological reserves, needed to maintain physiological and psychosocial homeostasis. Definition of physical frailty is based on the following criteria: unintentional weight loss, self-reported exhaustion, weakness, slow walking speed, and low physical activity, where 3 out of 5 these criteria confirms frailty. It is a dynamic, transitional process which constantly progresses, although it is potentially reversible. Frailty often co-exists with other severe diseases, affecting general well-being of the patient. Therefore, it is important for the family doctor to understand diagnosis and treatment to protect from an invasive procedure or potentially harmful medication, and prevent decline of functional independence. The aim of this review is to present current available treatment options and their effectiveness for frailty. Data from many observational studies were collected. The most beneficial seems to be combined multidisciplinary treatment including physical exercises, nutritional supplementation and cognitive training. Additionally, the further positive results of physical activity training on mobility, balance, coordination, muscle strength and reducing falls in frail elderly were also confirmed by many scientific reports. Pharmacological, nutritional, psychological and other interventions solely can also be helpful but the evidence is low. Preventive actions at many stages in the process leading to frailty can be applied.